Image and Graphics : 10th International Conference, ICIG 2019, Beijing, China, August 23–25, 2019, Proceedings, Part I /: 10th International Conference, ICIG 2019, Beijing, China, August 23–25, 2019, Proceedings, Part I. (2019) - Unknown
No abstract available